A escrita religiosa e homoerótica do poeta contemporâneo Waldo Motta - Santos, Ricardo Alves dos (2013)
This study aims at analyzing the literary project \"sacred eroticism\", by contemporary poet Waldo Motta, which was systematized in the work Bundo e outros poemas (Bundo and other poems, 1996), as an expressive response to the social annulment of the poet. The author s condition of homosexuality, poverty and discrimination become the subject of his lyric doctrine edification, in which the sacred element the poetry becomes a space of the homoaffective profane, thus using the poetic and the poetry to promote an elevation of homosexuality. In Waldo s poetry, sacred and profane are not separate instances, they inhabit the same place the anus which symbolically represents an alliance made between the self and the supreme being the poetry. In the sacredness of the poet s craft, we find an erotic and an profane language, and it establishes a revitalization of exclusion and protest discourses that subvert literary standards in pursuit to position itself poetically in relation to social and emotional problems resulting from a marginalized life.